2004
DOI: 10.1177/0734242x04042456
|View full text |Cite
|
Sign up to set email alerts
|

Oyster Shell as Substitute for Aggregate in Mortar

Abstract: Enormous amounts of oyster shell waste have been illegally disposed of at oyster farm sites along the southern coast of Korea. In this study to evaluate the possibility of recycling this waste for use as a construction material, the mechanical characteristics of pulverized oyster shell were investigated in terms of its potential utilization as a substitute for the aggregates used in mortar. The unconfined compressive strengths of various soil mortar specimens, with varying blending ratios of cement, water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 6 publications
(4 reference statements)
3
51
0
3
Order By: Relevance
“…In previous studies Yang et al 2005;Yoon et al 2004), it was reported that oyster shells are primarily composed of calcium carbonate (CaCO 3 ). Therefore, in this study, we evaluated the use of oyster shell waste as a liming material for the stabilization of metal-contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies Yang et al 2005;Yoon et al 2004), it was reported that oyster shells are primarily composed of calcium carbonate (CaCO 3 ). Therefore, in this study, we evaluated the use of oyster shell waste as a liming material for the stabilization of metal-contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lee et al (2009) and Kwon et al (2004) used oyster shell waste to remove phosphorus from wastewater, while Yang et al (2005) and Yoon et al (2004) studied its reuse as a construction material. The effects of oyster shell application on soil quality and crop production have also been studied by Lee et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The Korean government, concerned with public health, financed a project to increase recycling of this waste, because if this waste has been left untreated for a long time, it can be a source of nasty smell as a consequence of the decay of flesh remnants attached to the oyster or the microbial decomposition of salts into gases such as NH 3 , H 2 S and amines 5 . Many studies have investigated the use of oystershell waste as construction materials [6][7][8] . Another possibility for reuse of these shells is to use them as supplementary feeding [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…ture waste materials. Some researchers have explored the use of oyster shell waste as a substitute for aggregates in construction materials (Yoon et al 2003(Yoon et al , 2004Yang et al 2005), cement clinkers (Cheon and Song 2003), and fertilizers (Yoon et al 2003). Some facilities in Galicia use mussel shell waste mainly as input for their production processes, and also as a calcium carbonate source, fertilizer, cement clinker, poultry nourishment component, or water treatment agent.…”
Section: Responsible Editor: Ake Bergmanmentioning
confidence: 99%